Correlation between pH, buffering capacity, calcium and dental caries in schoolchildren - Zabokova Bilbilova, Efka; Sotirovska Ivkovska, Ana; Sarakinova, Olivera; Kokoceva Ivanovska, Olga; Stavreva, Natasha (Macedonian pharmaceutical bulletin, 2018)
The aim of this study was to determine salivary pH, buffering capacity and calcium levels in caries-free and caries-active children. We examined 80 children of both genders, 15 years of age. Subjects were divided into four groups as follows: caries-free females, caries-active females, caries-free males, caries-active males; each group consisted of 20 subjects. The unstimulated saliva sample was collected by the spitting method and then pH, buffering capacity and calcium in saliva was measured. The results showed that mean level of buffering capacity of saliva was decreased significantly in the caries-active group as compared to caries-free group. The obtained data showed that the mean levels of pH and calcium were decreased in the caries-active group as compared to the caries-free group, but the difference was not statistically significant. The saliva with its constituents plays an important role in maintaining oral and especially dental health. Salivary pH values were found to be higher in the caries-free group. In our study, there was no significant correlation of pH values and caries activity with gender. Buffer capacity values were significantly lower in the caries-active group than in the caries-free group. There were significant differences when the groups were compared in the caries-active group where buffer capacity values were higher in boys than in girls. Calcium content of saliva was higher in the caries-free group. The results obtained in this study related to the values of the pH, buffering capacity and calcium in saliva, may serve as parameters for determining the caries risk patients, and accordingly to plan and carry appropriate caries preventive measures. Keywords: saliva, dental caries, pH, buffer capacity, calcium